2012
DOI: 10.1111/j.1445-5994.2012.02931.x
|View full text |Cite
|
Sign up to set email alerts
|

Telerheumatology: an idea whose time has come

Abstract: Australia is a vast country with one‐third of the population living outside capital cities. Providing specialist rheumatologist services to regional, rural and remote Australians has generally required expensive and time‐consuming travel for the patient and/or specialist. As a result, access to specialist care for remote Australians is poor. Rheumatoid arthritis is a common disease, but like many rheumatic diseases, it is complex to treat. Time‐dependent joint damage and disability occur unless best evidence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 18 publications
1
33
0
1
Order By: Relevance
“…Since demand for care is predicted to increase, adoption of different models of care provision will be necessary [18,35,36]. These are likely to include telehealth and an increased emphasis on participatory health care where people with RA are active agents in the management of RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since demand for care is predicted to increase, adoption of different models of care provision will be necessary [18,35,36]. These are likely to include telehealth and an increased emphasis on participatory health care where people with RA are active agents in the management of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Apps that collect disease activity data using validated disease activity instruments may be useful in facilitating management with a rheumatologist by measuring medically credible RA activity between visits and potentially enabling some care to be provided via telehealth [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Leggett et al [3] examined the diagnostic accuracy and acceptability of telemedicine in the field of rheumatology and found that the televisual consultations were highly accurate (97%) and acceptable to patients, general practitioners, and specialists. Roberts et al [4] reported on the telerheumatology experience in Australia and emphasized the need for face-to-face consultations alongside teleconsultations to ensure that deficiencies in telehealth can be addressed in specific situations.…”
mentioning
confidence: 99%
“…Telemedicine, video conferencing, or otherwise improving access to existing practices, such as extending hours, may also play important roles in reducing travel times and thus improving access. 16,17,18 Interestingly, we found that some beneficiaries living in high-supply areas also traveled long distances to see a rheumatologist. Although more research is needed, we suspect that several factors may explain this paradox, including tertiary care referral patterns, patient preferences for particular, far-away clinicians, or lack of acceptance of public insurance.…”
Section: Discussionmentioning
confidence: 80%